2023
DOI: 10.31635/ccschem.022.202101741
|View full text |Cite
|
Sign up to set email alerts
|

Structural Isomerization in Cu(I) Clusters: Tracing the Cu Thermal Migration Paths and Unveiling the Structure-Dependent Photoluminescence

Abstract: Revealing structural isomerization in metal clusters would bridge huge structural gap between small molecular isomerization and solid-solid phase transformation. However, genuine structural isomerism in metal clusters is still rare. In this work, we report the first example of structural isomerism in Cu clusters. By utilizing the coordination flexibility of alkyne to enable the migration of partial Cu atoms in Cu metal cores, two Cu 15 cluster complexes (Cu 15 -a and Cu 15 -c) possessing identical composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The effects of the ligand type (difference in substituent groups) on the electronic structure, stability, and function of Cu clusters have been investigated [34,35] . Given that the strength of metallophilic interaction is comparable to the hydrogen bond, the metal core of the Cu cluster is flexible regarding the commonly used protecting ligands such as thiolates and alkynes [36] . As results, most of these studies are carried out on Cu clusters with different kernel structures [3,36,37] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of the ligand type (difference in substituent groups) on the electronic structure, stability, and function of Cu clusters have been investigated [34,35] . Given that the strength of metallophilic interaction is comparable to the hydrogen bond, the metal core of the Cu cluster is flexible regarding the commonly used protecting ligands such as thiolates and alkynes [36] . As results, most of these studies are carried out on Cu clusters with different kernel structures [3,36,37] .…”
Section: Introductionmentioning
confidence: 99%
“…[34,35] Given that the strength of metallophilic interaction is comparable to the hydrogen bond, the metal core of the Cu cluster is flexible regarding the commonly used protecting ligands such as thiolates and alkynes. [36] As results, most of these studies are carried out on Cu clusters with different kernel structures. [3,36,37] To obtain detailed information regarding ligand-directed properties, it is essential to synthesize Cu clusters with the same nuclearities but different kinds of ligands.…”
Section: Introductionmentioning
confidence: 99%
“…47−49 To overcome this issue, we conjure up a new strategy that combines the merits of CMCs and traditional metal nodes in metallacages: dual nodes for metallacages are expected to alleviate the stringent requirements of curvature of CMCs as nodes in whole-cage structure and to make use of the controllable coordination direction of traditional metal nodes. Considering the unlimited organic ligands that can be extended for additional metal nodes, 50,51 crown ether with the ability of directional coordination in cages.…”
mentioning
confidence: 99%
“…We found that pure organic ligands with −CC, −P, and −S directly chelating CMCs for cage structures are indeed difficult to control, because of the nondirectional coordination and sensitive metal–metal bonds which resulted in easy transformation or dissociation of CMCs due to slight variations in synthesis conditions. To overcome this issue, we conjure up a new strategy that combines the merits of CMCs and traditional metal nodes in metallacages: dual nodes for metallacages are expected to alleviate the stringent requirements of curvature of CMCs as nodes in whole-cage structure and to make use of the controllable coordination direction of traditional metal nodes. Considering the unlimited organic ligands that can be extended for additional metal nodes, , we focus on luminescent CMC-based spacers whose terminal groups are functionalized by carboxylate and crown ether with the ability of directional coordination in cages.…”
mentioning
confidence: 99%
“…Typically, polynuclear Cu clusters are synthesized using external protecting organic ligands, such as phosphines, amines, thiolates, and alkyls. As a result, some small Cu clusters, including several Cu 4 clusters, have been obtained. , However, most of these small Cu clusters are quite different in structure from the Cu Z cluster. Mankad reported several [Cu 4 S] clusters which have N 2 O reductase activities, opening the door for these bioinspired Cu clusters to their practical application in the conversion of greenhouse gases. , In addition, the known Cu clusters usually consist of Cu I centers which are generally sensitive to oxidation, making them easily agglomeration and deactivate during the catalytic process .…”
mentioning
confidence: 99%